Maastrichtse ceramiek : Merken en dateringen - Polling, A. (Lochem : De Tijdstroom, 1989)
Overzicht van de gebruikte merken van 1850-heden
P. Regout (De Sphinx), N.A. Bosch, Clairmont en Chainaye, Société Céramique, Guillaume Lambert, L. Regout (Mosa), F. Regout, Alfred Regout (Rema)